Coarsening mechanism of M2B-borides and their effect on the mechanical properties of high modulus steels - M. Gathmann; D. Moisi; H. Springer (Materials & Design, 2024)
Size, morphology and distribution of light and stiff, but inherently brittle particles are of critical importance for the property profile of high modulus steels. Powder atomisation can dramatically reduce the borides’ size to the nanoscale, but they typically coarsen substantially during annealing or compaction via hot isostatic pressing. This study investigated the effect of compaction parameters, namely temperature, pressure and time on the coarsening mechanism, porosity evolution and resultant mechanical properties of atomised Fe-Cr-B powder. Increasing annealing temperature and time from 950 to 1150 °C, respectively, 30 min to 8 h, resulted in a non-linear boride radius growth from 76 nm in the atomised state to 1.9 µm. Hot isostatic pressing, with additional pressures up to 140 MPa, decreased the pore size from about 5 to 0.2 µm. An optimised hot isostatic pressing processing window was defined at 1050 °C and 140 MPa, combining sufficiently reduced defects with a limited particle radius, and yielded in 730 MPa tensile strength at more than 20 % tensile elongation. Powder-metallurgical synthesis of Fe-Cr-B achieved similar properties to casted and hot-rolled material, by avoiding component size scaling effects of casting. The underlying phenomena and optimisation of high modulus steel production via powder metallurgy are discussed.